Sosialisasi Penggunaan Gadget Dalam Lingkungan Keluarga Jemaat GKPI Khusus Teladan - Irvan Rolyesh Situmorang; Hommy Dorothy Ellyany Sinaga; Frenky Situmorang; Petrus Loo (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2023)
The use of gadgets in the family environment has become an increasingly pervasive phenomenon in everyday life. This study aims to increase family members' understanding and awareness of positive impacts and the prevention of negative impacts. The socialization methods involved include the organization of eminars and group discussions with active participation from family members. Educational materials tailored to the needs of modern families are presented to provide the latest information about digital safety, positive benefits, and strategies for healthy use of gadgets in the family context. Preliminary findings show an increase in family members' understanding of the potential positive risks and benefits of using gadgets, as well as changes in behavior toward their use. Through an interactive and informative socialization approach, it is hoped that families can optimize the benefits of digital technology while maintaining balance and harmony in the household environment. The implications of this community service can be a guide for similar efforts to form a smart society through the use of gadgets in the family context